Andean tubers grown in Ecuador: New sources of functional ingredients. (June 2020) - Pacheco, M. Teresa; Hernández-Hernández, Oswaldo; Moreno, F. Javier; Villamiel, Mar
Abstract: Five unexplored Andean tubers grown in Ecuador were characterized. Yacon ( Smallanthus sonchifolius, var. INIAP-ECU-1247) showed a high level of prebiotic inulin-type fructooligosaccharides with a degree of polymerisation from 2 to 6 and the highest content of phenolic compounds. Mashua ( Tropaeolum tuberosum, var. INIAP-ECU-Izaño) showed high antioxidant capacity, attributed to its high carotenoid and vitamin C content. Melloco ( Ullucus tuberosus, var. INIAP-ECU-amarillo-rosa) had the highest content of fibre and crude protein, while purple sweet potato ( Ipomea batatas, var. INIAP-ECU-morado) and white carrot ( Arracacia xanthorrhiza, var. INIAP-ECU-blanca) showed a high yield of starch rich in amylose, with possible better functional properties than potato starch. Fructose, glucose and sucrose were found in all samples. These ancestral crops can be useful as non-traditional sources of bioactive compounds with applications in the development of biomaterials, pharmacological products or new functional ingredients.